An Unusual Case of Penile Spindle Cell Malignancy - Sri Aurobindo Prasad, Das (Cureus, 2018)
Sarcomatoid carcinomas are unusual high-grade tumors, predominantly composed of spindle cells. There appears to be no predilection for any specific site. A few cases of sarcomatoid tumors arising in the penis have been reported. We report a 60-year-old man with a pathological diagnosis of sarcomatoid carcinoma of the penis. This case reiterates the importance of including sarcomatoid carcinoma in the differential diagnosis, especially at uncommon sites.